Assessing New Diagnoses of HIV Among American Indian/Alaska Natives Served by the Indian Health Service, 2005-2014. (March 2018) - Reilley, Brigg; Haberling, Dana L.; Person, Marissa; Leston, Jessica; Iralu, Jonathan; Haverkate, Rick; Siddiqi, Azfar-E-Alam
Objectives: The objectives of this study were to use Indian Health Service (IHS) data from electronic health records to analyze human immunodeficiency virus (HIV) diagnoses among American Indian/Alaska Natives (AI/ANs) and to identify current rates and trends that can support data-driven policy implementation and resource allocation for this population. Methods: We analyzed provider visit data from IHS to capture all AI/AN patients who met a definition of a new HIV diagnosis from 2005 through 2014 by using International Classification of Diseases, Ninth Revision, Clinical Modification codes. We calculated rates and trends of new HIV diagnoses by age, sex, region, and year per 100 000 AI/ANs in the IHS user population. Results: A total of 2273 AI/ANs met the definition of newly diagnosed with HIV from 2005 through 2014, an average annual rate of 15.1 per 100 000 AI/ANs. Most (356/391) IHS health facilities recorded at least 1 new HIV diagnosis. The rate of new HIV diagnoses among males (21.3 per 100 000 AI/ANs) was twice as high as that among females (9.5 per 100 000 AI/ANs; rate ratio = 2.2; 95% confidence interval, 2.1-2.4); by age, rates were highest among those aged 20-54 for males and females. By region, the Southwest region had the highest number (n = 1016) and rate (19.9 per 100 000 AI/ANs) of new HIV diagnoses. Overall annual rates of new HIV diagnoses were stable from 2010 through 2014, although diagnosis rates increased among males ( P < .001) and those aged 15-19 ( P < .001), 45-59 ( P < .001), and 50-54 ( P = .01). Conclusions: New HIV diagnoses, derived from provider visit data, among AI/ANs were stable from 2010 through 2014. AI/ANs aged 20-54, particularly men, may benefit from increased HIV prevention and screening efforts. Additional services may benefit patients in regions with higher rates of new diagnoses and in remote settings in which reported HIV numbers are low.